Kantor Nirkabel sebagai Terobosan Budaya Kerja Baru bagi Pekerja Individual - Latif, Fauzia (Bina Nusantara University, 2012)
Today’s technology much influences people’s working environment. The current technology has created a working culture that is not rigid and conventional, but a flexible working environment, in terms of working site, how to work, and the products. A wireless office with its facilities is a breakthrough for both individual worker and teams in the modern era.